Drought survival of some perennial grasses in Mediterranean rainfed conditions: agronomic traits - Porqueddu C.; Nieddu S.; Maltoni S. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
A three-year experiment was carried out to evaluate perenniality and adaptive responses to drought of elite grass material from recent plant improvement work of Dactylis glomerata, Festuca arundinacea and Phalaris aquatica species, within the multi-site activity of the EU-PERMED project. The trial located in North Sardinia (Italy) on a calcareous sandy-loam soil was sown in October 2004 to compare 16 accessions. Measurements included: establishment, dry matter production, average row cover, sward senescence in late spring, plant and tiller density and phenology. Most cultivars established well. Plant density at establishment was higher in cocksfoots than fescues but from autumn 2005 tiller density was similar. Along the three years, fescues yielded significantly more than cocksfoots. Among P. aquatica accessions the cv. Partenope yielded almost 13 t/ha in the first year but did not survive summer drought. Plant re-establishment after summer drought was satisfactory for most accessions except D. glomerata cv. Porto. Results are encouraging, as several accessions combined a satisfactory yield potential with persistence under severe summer drought.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)